Avaliação do impacto assistencial e financeiro da genotipagem RHD fetal no plasma materno como ferramenta não-invasiva na conduta de atendimento a gestantes RhD negativo - Luciana Cayres Schmidt (2015)
Noninvasive RHD genotyping have been widely used as routine management of RhD negative pregnant women in developed countries. However, in Brazil, this test is not well known and they dont know nether to what impact the adoption of this tool could cause to the routine care of sensitized and non-sensitized pregnant RhD negative women. This study aims to avaliate the impact of the fetal RHD genotyping in the management of sensitized and non sensitized RhD negative pregnant women. Methods: 248 blood samples from RhD negative pregnant women were processed for fetal DNA purification. Real-time PCR was performed to amplify segments of exon 5 and 7 of the RHD gene. The results of genotyping in fetal maternal plasma were compared with the RhD phenotype of newborns. It was further raised the cost of the test and the impact of its adoption in routine care of sensitized and non-sensitized. pregnant RhD negative women. Results: The results of fetal RHD genotyping could be compared with 217 RhD phenotype of newborns. There were 9 inconclusive results, four false negative and 12 false positive. The sensitivity was 97.3%, the specificity was 82.1% and the acuracy of the test was 93.1%. The cost of fetal RHD genotyping was estimated in R$ 74,47. The estimated savings for the introduction of non-invasive molecular test for non-sensitized patients was approximately R$ 4,000.00 and for the sensitized women was around R$ 45,000,000.00. Conclusion: The fetal RHD genotyping test was sensitive and of low cost. The analysis of the impact of this introduction into routine care to non-sensitized and sensitized RhD negative pregnant women, has demonstrated that its introduction would be very advantageous by economic and welfare point of view. The financial impact for sensitized was much higher than for non- sensitized pregnant women. However, for non-sensitized pregnant women the possibility of administration of antenatal immunoprophylaxis would generate a substantial decrease of maternal sensitization with consequent reduction in the cost of monitoring those women at a future pregnancy.